MICROALGAE FOR CO2 REDUCTION AND WASTEWATER TREATMENT APPLICATION IN INDUSTRIAL AREA - Arif Dwi Santoso; Rahmania A. Darmawan; Joko P. Susanto (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
The microalgae incorporated photobioreactor (PBR) is a highly efficient biological system for converting carbon dioxide (CO2) gases into biomass and treating wastewater. In this study, the freshwater microalgae Chlorella sp. was cultured in two unit photobioreactors which were connected to a boiler of dairy factory. The source of water for microalgae culture media (in the photobioreactors) are collected from the waste water treatment plant of the dairy factory itself. The objective of this microalgae photobioreactor activity were to reduce CO2, produce biomass and as a part of a waste water treatment in a dairy industry in Indonesia. Both photobioreactors were operated for 14 days culture interval in the semi continuous cultivation, with initial stocking rate of 2 x 105 cells/ml microalgae. Carbon dioxide concentration from the boiler stack was 10-11 % vol. The photobioreactors were injected with the specified CO2 concentration with flow rate of 2 l/min. and 1.5 l/min. The result showed that microalgae photobioreactors capability in CO2 absorption were 0.78 ± 0.25 and 0.92 ±0.36 g CO2/l media/day, respectively. Before and after utilized by the photobioreactors system, Nitrate and Phosphate concentration of the culture media (supplied from the waste water treatment plant) decreased from 3-4 mg/l to 0.05-0.1 mg/l. After 14 days cultivation, biomass concentration of microalgae which were injected with CO2 flow rate of 2 l/min. and 1.5 l/min. were 19 x 106 cells/ml and 15 x 106 cells/ml respectively. Results showed that microalgal photobioreactors operated in an industrial area could reduce CO2 concentration and produce biomass.Keywords: photobioreactor (PBR), Chlorella sp., CO2 flue gas emissions, wastewater